Electronic structure investigation of wide band gap semiconductors—Mg2PN3 and Zn2PN3: experiment and theory. (3rd July 2020) - Al Fattah, Md Fahim; Amin, Muhammad Ruhul; Mallmann, Mathias; Kasap, Safa; Schnick, Wolfgang; Moewes, Alexander
Abstract: The research on nitridophosphate materials has gained significant attention in recent years due to the abundance of elements like Mg, Zn, P, and N. We present a detailed study of band gap and electronic structure of M2 PN3 (M = Mg, Zn), using synchrotron-based soft x-ray spectroscopy measurements as well as density functional theory (DFT) calculations. The experimental N K-edge x-ray emission spectroscopy (XES) and x-ray absorption spectroscopy (XAS) spectra are used to estimate the band gaps, which are compared with our calculations along with the values available in literature. The band gap, which is essential for electronic device applications, is experimentally determined for the first time to be 5.3 ± 0.2 eV and 4.2 ± 0.2 eV for Mg2 PN3 and Zn2 PN3, respectively. The experimental band gaps agree well with our calculated band gaps of 5.4 eV for Mg2 PN3 and 3.9 eV for Zn2 PN3, using the modified Becke–Johnson (mBJ) exchange potential. The states that contribute to the band gap are investigated with the calculated density of states especially with respect to two non-equivalent N sites in the structure. The calculations and the measurements predict that both materials have an indirect band gap. The wide band gap of M2 PN3 (M = Mg, Zn) could make it promising for the application in photovoltaic cells, high power RF applications, as well as power electronic devices.